Optimalisasi Keterampilan Higher Order Thinking Skills (HOTS) Peserta Didik melalui Model Discovery Learning Berbantuan Laboratorium Virtual Berbasis Smartphone: Optimizing Students' Higher Order Thinking Skills (HOTS) through the Discovery Learning Model Assisted by Smartphone-Based Virtual Labs - Irani Diansah; Hamatun Hamatun; Dwi Wulandari (Pendidikan Fisika Universitas Nurul Huda, 2026)
Higher Order Thinking Skills (HOTS) are essential competencies in 21st-century learning. However, students often experience difficulties in analyzing physics concepts due to limited laboratory activities and teacher-centered learning. This study aimed to determine the effectiveness of Discovery Learning assisted by a smartphone-based virtual laboratory in improving students’ HOTS. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The participants consisted of 44 students of MTs Darul A'mal Lampung, divided into an experimental class (24 students) and a control class (20 students). Data were collected through HOTS tests in the form of pretest and posttest. Data analysis included descriptive statistics, Mann–Whitney U tests, and effect size analysis. The experimental class achieved a higher posttest mean score (87.08) than the control class (71.50). The normalized gain score of the experimental class (0.67) was also higher than that of the control class (0.42). The Mann–Whitney U test showed a significant difference between the two groups (Z = -3.444), with an effect size value of 0.519 indicating a large effect. Discovery Learning assisted by a smartphone-based virtual laboratory can be used as an alternative instructional strategy to improve students’ HOTS in physics learning